Socioeconomic and health care coverage disparities in children, adolescents, and young adults with sarcoma. Issue 12 (17th September 2020) - Westermann, Carly; Weller, Jennine; Pedroso, Felipe; Canner, Joe; Pratilas, Christine A.; Rhee, Daniel S.
Abstract: Background: Socioeconomic and health care coverage disparities are established as poor prognostic markers in adults with sarcoma, but few studies examine these differences among pediatric, adolescents and young adults (AYA). This study examines the association between socioeconomic status (SES), insurance status, and disease presentation among children and AYA patients with sarcoma. Methods: This is a retrospective cohort study of patients aged 0‐25 years with bone or soft tissue sarcoma from the National Cancer Database. SES assignments were based on estimated median income and education level. Patient demographics and clinical factors were compared by SES and insurance status. Multivariate logistic regression models were fitted to determine adjusted odds ratios of SES and insurance status on metastatic disease or tumor size ≥5 cm at time of presentation. Results: In a cohort of 9112 patients, 2932 (32.1%) had low, 2084 (22.8%) middle, and 4096 (44.9%) high SES. For insurance status, 5864 (64.3%) had private, 2737 (30.0%) public, and 511 (5.6%) were uninsured. Compared to high SES, patients with low SES were more likely to have metastatic disease (OR = 1.16, P  = .03) and tumors ≥5 cm (OR = 1.29, P  < .01). Compared to private insurance, public and no insurance were associated with metastatic disease (OR = 1.35, P  < .01 and OR = 1.32, P  = .02) and increased tumors ≥5 cm (OR = 1.28, P  < .01 and OR = 1.67, P  < .01). Conclusions: SES disparities exist among children and AYA patients with sarcoma. Low SES and public or no insurance are associated with advanced disease at presentation. Further studies are needed to identify interventions to improve earlier detection of sarcomas in at‐risk children and young adults.